Fintech for the Masses: Mapping Digital Financial Inclusion Research in Developing Countries - Sarmiento, Allen Grace M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Digital Financial Inclusion has emerged as a critical driver for sustainable development, leading to a rapid expansion of academic literature. However, this burgeoning work lacks a comprehensive overview, resulting in a fragmented scholarly landscape. This study addresses this gap by employing a bibliometric analysis to systematically map the intellectual structure and thematic evolution of digital financial inclusion research in developing countries. Using VOSviewer software, co-citation and co-word analysis were conducted to identify the field's foundational works and dominant research themes. The co-citation analysis reveals six influential intellectual clusters, including financial inclusion measurement, the transformative role of mobile technology, behavioral models of technology adoption, and the importance of institutional economics. The co-word analysis identifies five major thematic clusters centered on technological innovation and adoption, sustainability and human development, the evolving financial system, core digital financial inclusion mechanisms, and macroeconomic outcomes like economic growth and poverty reduction. The resulting intellectual map serves as a valuable guide for researchers to identify trends and gaps, and for policymakers to make evidence-based decisions to foster a more inclusive financial ecosystem.